Guidelines for Enhancing the Efficiency of New Public Management of Village Committee in Doi-Ngam Subdistrict, Phan District, Chiang Rai Province - Sirichaiwattanakul, Patterata; Imiwat, Prayoon; Sommanasak, Waraduang (Journal of Public Administration Chiang Rai Rajabhat University, 2025)
This research aims to 1) study the new public management and problems in the performance of village committees in Doi Ngam Subdistrict, Phan District, Chiang Rai Province.2) To propose guidelines to promote the efficiency of new public management of village committees in Doi Ngam Subdistrict, Phan District, Chiang Rai Province, with a population of 180 people from 14 village committees of Doi Ngam Subdistrict, Phan District, Chiang Rai Province.Data analysis was performed using descriptive statistics, including percentages, means, and standard deviations. The results of the study found that the population group had opinions about the guidelines for promoting efficiency in new public administration. There were 2 objectives: 1) To study new public administration and problems in the performance of the village committees from all 7 areas, namely: Including (1) Administration for the benefit of the people (2) Administration to achieve results in the missions of the state (3) Administration with efficiency and value for money in terms of the missions of the state (4) Reducing work procedures (5) Improving the missions of government agencies (6) Facilitating and responding to the needs of the people (7) Evaluating government performance results of the study found that the areas that should promote the efficiency of new public management include: In terms of government administration, it is effective and worthwhile in terms of government missions, in terms of reducing work procedures, and in terms of evaluating government performance. And from the presentation of research results that led to group discussions with key informants. Objective 2) Propose guidelines to promote efficiency in new public administration. The results of the study found that there should be assignments, operational plans, budgets, and decision-making regarding orders. Approval or other action, responsibility for direct action, clarity of roles and missions in performing duties and to lead to further development.